2023
DOI: 10.1175/jas-d-21-0275.1
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Numerical Benchmark for Warm Rain Processes

Abstract: The Kinematic Driver-Aerosol (KiD-A) intercomparison was established to test the hypothesis that detailed warm microphysical schemes provide a benchmark for lower-complexity bulk microphysics schemes. KiD-A is the first intercomparison to compare multiple Lagrangian cloud models (LCMs), size bin-resolved schemes, and double-moment bulk microphysics schemes in a consistent 1D dynamic framework and box cases. In the absence of sedimentation and collision-coalescence, the drop size distributions (DSDs) from the L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Hill et al. (2023) demonstrated that the DSDs in warm rain processes are sensitive to the selection of the collision‐coalescence model. Although testing the sensitivity of simulated cloud properties to the collision‐coalescence model could be a valuable direction for future research, in this study we focus on trends in the LWC and collision‐coalescence rate in response to changes in chamber configuration.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hill et al. (2023) demonstrated that the DSDs in warm rain processes are sensitive to the selection of the collision‐coalescence model. Although testing the sensitivity of simulated cloud properties to the collision‐coalescence model could be a valuable direction for future research, in this study we focus on trends in the LWC and collision‐coalescence rate in response to changes in chamber configuration.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Finally, it is important to acknowledge that, while the primary goal of this work is to examine factors that can enhance collision-coalescence in a cloud chamber, the collision-coalescence model used in bin microphysics may not be entirely accurate. Hill et al (2023) demonstrated that the DSDs in warm rain processes are sensitive to the selection of the collision-coalescence model. Although testing the sensitivity of simulated cloud properties to the collision-coalescence model could be a valuable direction for future research, in this study we focus on trends in the LWC and collision-coalescence rate in response to changes in chamber configuration.…”
Section: Journal Of Advances In Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Both methods use bins to make sampling of the initial aerosol radius more even, but differ in the way the entire bin range is selected. Recently, Hill et al (2023) found differences in precipitation between different implementations of particle microphysics, both using AON and binned initialization. Differences in details of bin initialization were proposed as one of potential reasons for the observed discrepancies.…”
Section: Sensitivity To Sd Initialization Methodsmentioning
confidence: 99%
“…PySDM supports a PyMPDATA-based (Bartman, Banaśkiewicz, et al, 2022) reimplementation of the 1D kinematically-driven test framework in a recently-published intercomparison of microphysics methods (Hill et al, 2023). The authors are unaware of recent SDM algorithm implementations in open-source packages beyond those mentioned in (Bartman, Bulenok, et al, 2022) and the related list of links in the PySDM README file.…”
Section: Relevant Recent Open-source Developmentsmentioning
confidence: 99%